2001
DOI: 10.1159/000054867
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Interleukin-1β, Interleukin-6, Soluble Interleukin-2 Receptor and Tumor Necrosis Factor α of Depressed Patients in Japan

Abstract: There are a number of investigations which indicate the important relationship between depression and cytokines. In this study, we investigated plasma interleukin (IL)-1β, IL-6, soluble IL-2 receptor (sIL-2R) and tumor necrosis factor (TNF)-α of depressed patients whose clinical evaluation was performed by the Hamilton Rating Scale for Depression (HAM-D) and the Profile of Mood States (POMS). They were compared with those of the control subjects, and before and after treatment with antidepressants. Before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 19 publications
3
40
1
1
Order By: Relevance
“…106 Contradictory results are very few indicating reduced, 107 or not altered, serum IL-6 levels. 97,108,109 The potential influence of possibly interfering variables, such as age, smoking, gender, recent infections and prior medication (including insufficient washout period) to IL-6 release and concentration must be considered. 110 An agerelated increase of IL-6 serum values was reported in patients with MD, 111 but also elderly depressed patients exhibit higher IL-6 serum levels compared with control persons of comparable age.…”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 99%
“…106 Contradictory results are very few indicating reduced, 107 or not altered, serum IL-6 levels. 97,108,109 The potential influence of possibly interfering variables, such as age, smoking, gender, recent infections and prior medication (including insufficient washout period) to IL-6 release and concentration must be considered. 110 An agerelated increase of IL-6 serum values was reported in patients with MD, 111 but also elderly depressed patients exhibit higher IL-6 serum levels compared with control persons of comparable age.…”
Section: The Inflammatory Hypothesis Of Depressionmentioning
confidence: 99%
“…Indeed, treatment with SSRIs has been shown to decrease MD associated cytokine elevations. In particular, the levels of inflammatory cytokines IL-1β, IL-6 and TNFα have been reported to be reduced following SSRI treatment (Basterzi et al, 2005;Kagaya et al, 2001;Lanquillon et al, 2000;Leo et al, 2006;Tuglu et al, 2003;Yoshimura et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, though many studies showed that antidepressants have anti-inflammatory effects (Basterzi et al, 2005;Kagaya et al, 2001;Lanquillon et al, 2000;Leo et al, 2006;Tuglu et al, 2003;Yoshimura et al, 2009), an increasing number of studies are reporting a proinflammatory action (Chen et al, 2010;Haastrup et al, 2012;Hannestad et al, 2011;Jazayeri et al, 2010;Kim et al, 2013;Song et al, 2009). In addition, the bi-directional crosstalk between SSRI administration and inflammation has been described also by studies investigating the effects of antiinflammatory drugs on antidepressant efficacy.…”
mentioning
confidence: 99%
“…Furthermore, cerebrospinal IL-1beta levels were correlated with the severity of depression (Levine et al, 1999), age of onset (Anisman et al, 1999), and duration of illness (Anisman et al, 1999). However, several studies have found that the IL1beta levels were unchanged in MDD patients (Rothermundt et al, 2001;Kagaya et al, 2001;Brambilla and Maggioni, 1998) and were not correlated with the severity of depression (Rothermundt et al, 2001). Furthermore, Weizman et al (1994) found a significant reduction in IL-1beta production in untreated MDD patients compared to normal controls and a significant increase of IL-1beta synthesis after drug treatment.…”
Section: Introductionmentioning
confidence: 99%